Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Klinik Gigi Niti Bekasi - Azahro Nurfatin Al Afifah, Luthfialita; Gofur, Abdul (JAMBIS : Jurnal Administrasi Bisnis, 2024)
From the phenomenon that occurred at the Niti Dental Clinic Bekasi, Researchers found that the ups and downs of customers in carrying out medical treatment, especially dental treatment, is a problem at the Niti Dental Clinic Bekasi, so that resulting in customer satisfaction which is expected to stabilize the clinic’s income. This research was useful to know the quality of servis and price on customer satisfaction at Niti Dental Clinic Bekasi. The type of research carried out utilized descriptive quantitative. The population in the research carried out were patients who visited for dental treatment at Niti Dental Clinic Bekasi. The sample used was 127 respondents using purposive sampling technique. The analysis tool utilized multiple linear regression. The result of the research determined that the result of t-test service quality for a number of hypotheses testing findings for service quality variables showed that the t-count value exceeded the t-table (9.464>1.657) with a significance level of 0.000<0.05, so that Ho was rejected, and Ha was accepted. The result of the simultaneous test of the service quality and price variables showed that the F-count value exceeded the F-table (232.741>3.07) with a significance level of 0.000<0.05. So, it can be concluded that the variables of service quality and price simultaneously had a positive and significant influence on customer satisfaction of 82,6%.